Kritik Wacana Tafsir tentang HAM - Subur Wijaya (LP2M Universitas PTIQ Jakarta, 2018)
This article discusses the study of Human Rights discourse on all kinds of physical and psychological violence resulting from gender bias practices towards the role and position of women in a family that is legally not allowed based on the international declaration on Human Rights, because the violation ignores the basic rights of individuals. Domestic violence, as one of the examples of gender bias, is legally banned due to subordination, marginalization and stereotype against men or women in the context of domestic (household) contexts. Therefore, the division of gender roles refers to the rights and obligations of husbands under the normative religious doctrine and intolerant socio-cultural understanding can be categorized as violating human rights law. In the Islamic sense of Human Rights it is actually whether new or foreign, because the discourse about human rights in Islamic advancement is earlier compared to other concepts or teachings, thus Islam comes inherently bringing the teaching of human rights. Islamic teachings on human rights can be found in the main sources of Islamic teachings i.e., al-Qur’an and Hadith which are the source of normative teachings, also found in the practice of the life of Muslims.